Sistem Budidaya Rumput Laut Gracilaria verrucosa di Pertambakan dengan Perbedaan Waktu Perendaman di Dalam Larutan NPK - Rukmi, Ayuning Smita; Sunaryo, Sunaryo; Djunaedi, Ali (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Seaweed, Gracilaria verrucosa, is a plant that could be live in the brackishwater pond also requires nutrients in sufficient quantities and balanced in order to achieve optimal production. Therefore, fertilizer treatment on this commodity is very necessary for increasing production. This study was designed by Completely Randomized Design (CRD) with immersion period treatment the G. verrucosa of the NPK solution. The treatments, namely used: A. Control, B. 10 minutes, C. 20 minutes, D. 30 minutes, E. 40 minutes, F. 50 minutes, G. 60 minutes immersion. This study used N organic total (nitrite, nitrate and ammonium) that was obtained from NPK fertilizer with concentration of 0,6 mg/L. Planting was done by using longline method of 72 ties and was reared for 35 days. The results showed that there was significant effect of NPK immersion time on the growth rate of G. verrucosa (p<0,01). The highest average of specific growth rate of G. verrucosa in the treatment G, which was 2,13% per day and average of specific growth rate G. verrucosa lowest in treatment A, which was 1,67% per day.